Private finance - Jenkinson, T (2003)
This paper considers the arguments for and against private‐sector financing—as opposed to operational management—of public services. Under certain conditions the costs of public and private finance will be similar, but these conditions are unlikely to hold for many public services. Using examples from the UK, we show how decisions to introduce private financing are often political, with little economic rationale.